The Measurement and Improvement of Effectiveness in K-440 Haul Truck Using Overall Equipment Effectiveness in Coal Mining Company - Kurniawan, Shelvy; Azaria, Ayesha; Alzena, Talitha; Dwicahyo, Yandri Habib (ComTech: Computer, Mathematics and Engineering Applications, 2019)
The objectives of this study were to determine the effectiveness of K-440 haul trucks based on Overall Equipment Effectiveness (OEE) calculation, to find out the main factors that caused the ineffectiveness of K-440 haul trucks based on fishbone diagram and Failure Mode and Effect Analysis (FMEA), and to analyze the proposed implementation of appropriate improvements to overcome the main problems of K-440 haul trucks. The method used was the mixed method, and the type of research was descriptive. The analysis methods used were OEE, fishbone diagram, and FMEA. The results show that the average effectiveness of the three K-440haul trucks is still far below international standards, which is 44,99%. The material is a significant factor that causes low OEE based on fishbone diagram analysis. There are five problems based on the Risk Priority Number (RPN) critical value from FMEA analysis, namely transmission which is not functioning properly, worn brake lining, unrotated propeller shaft on the shaft, cracked brake drum, and broken spring. Then, the implementation of eight pillars of Total Productive Maintenance (TPM) is proposed in overcoming the main problem of K-440haul trucks. Based on these results, the company needs to implement eight pillars of TPM and carry out OEE calculations regularly.